2021
DOI: 10.1016/j.infpip.2021.100133
|View full text |Cite
|
Sign up to set email alerts
|

Disinfecting handheld electronic devices with UV-C in a healthcare setting

Abstract: Summary Handheld Electronic Devices (HEDs) play a central role in the hospital environment. However, they can be a vehicle for transmitting (pathogenic) microorganisms. We studied whether disinfection with UV-C light is successful in disinfecting three different HEDs in a clinical setting. Disinfection with UV-C light was performed with the UV-Smart® D25. We took a total of 800 samples on two departments and counted colony forming units. More than half of the baseline measurements were moderately (>… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…A previous study identified a potential risk with mobile devices and recommended that the routine disinfection of these devices should be incorporated into infection control standards which can significantly reduce the incidence of nosocomial infections presently reported in medical facilities. 13,[29][30][31] Thirdly, the use of those devices during the COVID-19 pandemic was even more challenging. There was an exponential increase in the use of electronic devices during the COVID-19 pandemic due to its accessibility of patient information for staff in isolation facilities, allowing them to participate in virtual ward rounds and support front-line staff with clinical advice and administrative support and their use in telehealth services.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study identified a potential risk with mobile devices and recommended that the routine disinfection of these devices should be incorporated into infection control standards which can significantly reduce the incidence of nosocomial infections presently reported in medical facilities. 13,[29][30][31] Thirdly, the use of those devices during the COVID-19 pandemic was even more challenging. There was an exponential increase in the use of electronic devices during the COVID-19 pandemic due to its accessibility of patient information for staff in isolation facilities, allowing them to participate in virtual ward rounds and support front-line staff with clinical advice and administrative support and their use in telehealth services.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, 44 (62%) of the faculty were men, and 27 (38%) were women. Trainees were younger, with a median age of 28 (26)(27)(28)(29)(30)(31)(32)(33)(34) and 47 (39-55) for faculty. Out of the PGTs, 67 (77.9%) of the respondents were residents, and 19 (22.1%) were clinical fellows.…”
Section: Characteristics Of Participantsmentioning
confidence: 99%
“…These results indicate that using the sanitizer once or twice a day can result in consistently decreased contamination of smartphones. 1 Davis spoke to the importance of considering human factors and workflows when selecting which disinfection modality for mobile devices might be best. "With UV sanitizers, for example, you put your mobile device in it usually for 30 seconds to two minutes, which can be an eternity for a nurse," he said.…”
Section: Ultraviolet Lightmentioning
confidence: 99%
“…Due to the necessary direct contact of human fingers with the touchscreen, the release and ingestion of microorganisms (including pathogens) is virtually unavoidable. Therefore, it is not surprising that various studies find microbial contamination on up to 100% of touchscreens and that there is concern that such screens are potential vectors of infection [ 1 ], [ 2 ], [ 3 ], [ 4 ], [ 5 ], [ 6 ], [ 7 ], [ 8 ]. Consequently, touchscreen disinfection is recommended or even demanded [ 4 ], [ 9 ], [ 10 ], [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…UVC exhibits the strongest antimicrobial effect by damaging the DNA and RNA of all microorganisms without exception. Disinfection by ultraviolet radiation is a process that can be performed in minutes or even seconds given sufficient irradiance [ 8 ], [ 14 ], [ 15 ], [ 16 ], [ 17 ], [ 18 ], [ 19 ], [ 20 ], [ 27 ], [ 28 ]. Conceivable applications are those in which this could happen automatically even between two users, e.g., by irradiating the touchscreen from above or from the side, or scanning it as described by Alhmidi et al [ 27 ].…”
Section: Introductionmentioning
confidence: 99%